MENAKSIR KUALITAS LAYANAN DAN PENGARUHNYA TERHADAP KEPUASAN PELANGGAN - Akmal Abdullah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2011)
This research aims (1) to know and analyze the influence of Service Quality Dimensions at Clarion Hotel and Convention Makassar, (2) to know what dimension that mostly influence the service quality of customer. This research is a survey towards Customer of Clarion Hotel and Convention Makassar. Analysis unit in this research is individual. Sample selection is y using Random Sampling method. The observed variable is (1) customer’s satisfaction, (2) realibility, (3) responsibility , (4) assurance, (5) emphaty, and (6) tangible. The obtained data then analyzed by using multiple regression with calculation through computer with SPSS. The results show that (1) the results of statistic test that simultanously reability, responsibility, assurance, emphaty and tangible influence towards the customer satisfaction of Clarion Hotel and Convention Makassar. (2) partially show that service quality in form of responsibility give the most contribution towards the level of customer satisfaction.